PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING DENGAN PENDEKATAN TARL (TEACHING AT THE RIGHT LEVEL) - Mukarramah, Mukarramah; Nisa, Firda Khoirun; Azizah, Izza; Manuharawati, Manuharawati; Utami, Indah Desi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to improve the mathematics learning outcomes of students in class X-9 SMAN 15 Surabaya semester 2 of the 2023/2024 academic year using the PBL (Problem Based Learning) learning model with the TaRL (Teaching at The Right Level) approach. PTK (Classroom Action Research) was carried out in 2 cycles. The subjects in this research were students in class X-9 at SMAN 15 Surabaya, totaling 35 students. The variables in this research consist of the independent variable, namely the PBL learning model with the TaRL approach, while the dependent variable is the students' mathematics learning outcomes. The data analysis technique uses comparative descriptions in the form of percentages of mathematics learning outcomes in the pre-cycle, cycle I and cycle II. Based on the research results, it can be concluded that learning using the PBL (Problem Based Learning) model with the TaRL (Teaching at The Right Level) approach can improve students' mathematics learning outcomes in statistics material (mean and mode of single data and group data). The results before action was taken were that in the pre-cycle only 14 students or 40% completed, in cycle I this increased to 20 students or 57% who completed and in cycle II it increased again to 28 students or 80% of students who completed. This research was said to be successful because it achieved a student graduation percentage of above 78%. Keywords: Problem Based Learning, Teaching at the Right Level, Mathematics Learning Outcomes